Effectiveness of Purple Cabbage Flower (Brassica oleracea var. capitata f. rubra) Extract as a Natural Indicator for Borax Identification in Food Products - Fauziah Indira Siregar; Rahel Nainggolan; Nayla Azizah; Teresia Vredemika Sidauruk; Miquel Kaban; Larasati Arum Utami; Nurbaity Situmorang (MO.RI Publishing, 2026)
The misuse of borax as a preservative in school snacks poses a serious threat to food safety, necessitating practical and accessible solutions for the general public. This study aimed to evaluate the effectiveness of purple cabbage (Brassica oleracea var. capitata f. rubra) extract as a natural indicator for the qualitative detection of borax. Laboratory experiments were conducted at the Biology Laboratory of Universitas Negeri Medan using the maceration method with water as the solvent to extract anthocyanin pigments. Food samples tested included meatballs, tofu, yellow noodles, and crackers. The results showed that purple cabbage extract successfully detected borax in yellow noodle samples through a colour change from purple to bluish-green, caused by the deprotonation of anthocyanins under alkaline conditions. These findings demonstrate that purple cabbage extract is a valid, economical, practical, and environmentally friendly screening tool to support public food safety monitoring.